Risk assessment in patients with acute alcohol intoxication - Grüttner, Joachim; Walter, Thomas; Lang, Siegfried; Reichert, Miriam (In vivo, 2015)
Aim: Patients with acute alcohol intoxication present a serious and still growing problem for pre- and intra-hospital emergency services. Data on the clinical risk assessment of alcohol-intoxicated patients are sparse. The aim of the present work was, therefore, to collect and assess relevant risk parameters. Materials and Methods: At the Mannheim University Hospital, the medical records of 844 alcohol-intoxicated Emergency Department patients were retrospectively studied and evaluated. Results: The patients with alcohol intoxications were predominantly males with an average age of 45 years. Mean blood alcohol concentration was 0.28%. The rate of haemodynamic, respiratory or metabolic complications in these patients was low. In 43% of cases, there was moderately to severely impaired consciousness. About half of the patients were treated on an outpatient basis. Conclusion: Our data demonstrate a low clinical risk for alcohol-intoxicated patients. Nevertheless, it is necessary to provide a defined monitoring standard in order to also be prepared for the few potential complications of alcohol intoxication and the possible differential diagnoses of impaired consciousness.
Gesehen am 08.09.2017